2016
DOI: 10.1098/rspb.2016.0671
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling anisogamy: egg size and ejaculate size mediate selection on morphology in free-swimming sperm

Abstract: Gamete dimorphism (anisogamy) defines the sexes in most multicellular organisms. Theoretical explanations for its maintenance usually emphasize the size-related selection pressures of sperm competition and zygote survival, assuming that fertilization of all eggs precludes selection for phenotypes that enhance fertility. In external fertilizers, however, fertilization is often incomplete due to sperm limitation, and the risk of polyspermy weakens the advantage of high sperm numbers that is predicted to limit sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
(118 reference statements)
2
15
1
Order By: Relevance
“…overall sperm size; Humphries et al, ). Our findings also add to a growing number of studies that support this prediction (Fitzpatrick, Simmons, & Evans, ; Lymbery et al, ; Monro & Marshall, ). As such, measuring nonlinear selection on multivariate sets of sperm traits is likely to be a necessary (though sometimes complicated) step in assessing selection on sperm morphologies and predicting their adaptation to a changing world.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…overall sperm size; Humphries et al, ). Our findings also add to a growing number of studies that support this prediction (Fitzpatrick, Simmons, & Evans, ; Lymbery et al, ; Monro & Marshall, ). As such, measuring nonlinear selection on multivariate sets of sperm traits is likely to be a necessary (though sometimes complicated) step in assessing selection on sperm morphologies and predicting their adaptation to a changing world.…”
Section: Discussionsupporting
confidence: 84%
“…For males, fertility relies on the ability of sperm to collide and fuse with eggs; hence, selection has ample scope to target sperm traits that are involved in fertilization (Simmons & Fitzpatrick, ). Indeed, in a range of taxa, various aspects of sperm morphology play important roles in mediating sperm swimming performance (Lüpold, Calhim, Immler, & Birkhead, ; Malo et al, ), and ultimately male fertility (Lymbery, Kennington, & Evans, ; Monro & Marshall, ). For instance, sperm swimming speed is dictated by counteracting forces of thrust produced by the tail versus drag produced by the head and midpiece, which respectively house the nucleus and mitochondria (Humphries, Evans, & Simmons, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of recent studies have employed such approaches in external fertilizers and reported complex patterns of multivariate selection on sperm phenotypes (Fitzpatrick, Simmons, & Evans, 2012; Johnson, Monro, & Marshall, 2013; Lymbery, Kennington, & Evans, 2018). For example, using an experimental approach that manipulated the size of gametes at fertilization, Monro and Marshall (2016) reported that egg and ejaculate size independently mediate patterns of selection on sperm morphology. However, we are unaware of any studies that have formally determined whether the form and direction of selection depend on external changes to sperm phenotypes, such as those induced by female‐derived chemicals, in a multivariate framework.…”
Section: Introductionmentioning
confidence: 99%
“…Like many aquatic ectotherms, Galeolaria has sessile adults but planktonic gametes, embryos, and larvae, whose vulnerability to environmental stress makes them bottlenecks for population persistence under climate change (Pandori and Sorte 2019). Adult Galeolaria breed year‐round by spawning eggs and sperm into the external water column, where they must fuse for fertilization (Monro and Marshall 2016; Chirgwin et al. 2020), and where embryos and larvae also develop before eventually settling and recruiting into sessile adult populations.…”
Section: Methodsmentioning
confidence: 99%